204 Glycomimetics; A Novel Class of Drugs to Protect Against Free Fatty Acid-Induced Endothelial Dysfunction. (3rd June 2016) - Wilkinson, Fiona L; Mahmoud, Ayman; Jones, Alan M; Wilkinson, James; Romero, Miguel; Duarte, Juan; Yvonne Alexander, M
Abstract : Background: Endothelial dysfunction is a key player in cardiovascular disease (CVD) complications and novel drugs are required to treat this pathological process. Glycosaminoglycans (GAGs) are key molecules that regulate signalling in many biological processes and drugs that mimic their structure could be a novel source of therapeutics to target specific CVD pathways. Purpose: We have synthesised a set of four glycomimetic compounds and our objective was to determine whether they could activate protective pathways in endothelial cells subjected to fatty acid-induced endothelial dysfunction. Methods: Glycomimetics, C1-C4, were synthesised by the stepwise transformation of 2, 5-dihydroxybenzoic acid to a range of 2, 5-substituted benzoic acid derivatives, incorporating the key sulphate groups to mimic heparan sulphate. Human Umbilical Vein Endothelial Cells (HUVECs) were treated with glycomimetics (1ÂµM) in the presence or absence of the free fatty acid, palmitate. DAF-2 and H2 DCF-DA assays were used to determine NO and reactive oxygen species (ROS) production, respectively. Lipid peroxidation colorimetric and antioxidant enzyme activity ssays were also carried out. RT-PCR and western blotting were utilised to measure Akt, eNOS, Nrf-2, NQO-1 and HO-1 expression. Endothelial function was determined ex vivo using acetylcholine-induced endothelium-dependent relaxation in mouse thoracic aortic rings by wire myography. Results: All four g lycomimetics protected against palmitate-induced oxidative stress and enhanced NO production in vitro via upregulation of Akt/eNOS signalling, activation of the Nrf2/ARE pathway and down-regulation of ROS-induced lipid peroxidation. Under palmitate-induced oxidative stress, ex vivo endothelium-dependent relaxation was significantly enhanced by all four glycomimetics. Furthermore, the glycomimetics did not induce HUVEC activation, as determined by lack of ICAM-1 protein. Conclusion: We have developed a new set of small molecule glycomimetics that do not activate ECs and protect against free fatty acid-induced endothelial dysfunction both in vitro and ex vivo . Future work will focus on developing the glycomimetics into drug-like therapies that target endothelial damage.